2021
DOI: 10.1101/2021.02.24.432694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid adaptation and remote delivery of undergraduate research training during the COVID 19 Pandemic

Abstract: COVID-19 continues to alter daily life around the globe. Education is particularly affected by shifts to distance learning. This change has poignant effects on all aspects of academic life, including the consequence of increased mental stress reported specifically for students. COVID-19 cancellations of many summer fellowships and internships for undergraduates across the country increased students' uncertainty about their educational opportunities and careers. When the pandemic necessitated elimination of on-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Students perceived gains in their skills to be a direct result of their research experience. These findings concur with other studies that found that remote undergraduate research experiences developed students' skill confidence and increased their interest in STEMM careers (Speer et al, 2021;Yang Yowler et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Students perceived gains in their skills to be a direct result of their research experience. These findings concur with other studies that found that remote undergraduate research experiences developed students' skill confidence and increased their interest in STEMM careers (Speer et al, 2021;Yang Yowler et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Beyond promoting cohort cohesiveness, these structured events provide a daily and weekly framework that facilitates the development of time management skills and function as milestones for trainees to monitor their progress. While the content of many of these events was readily transitioned to a virtual format, replicating the interpersonal interactions that are central to effective community building in an online setting required novel approaches and mechanisms [ 5 , 6 , 9 ]. To address this challenge, we took a multifaceted approach in which new online components focused on mentoring, trainee interactions, and holistic wellness.…”
Section: Resultsmentioning
confidence: 99%
“…New and existing approaches promoted online trainee engagement in group settings that included inter-programmatic, program-specific, or research group contexts. However, COVID restrictions necessitated an increase in research and education components that were performed independently and, in turn, presented a trainee-specific set of challenges that reflected individual learning styles and prior experience in a virtual research environment [ 6 , 12 ]. To address such issues that may not be evident in group settings, program directors and coordinators scheduled a series of one-on-one meetings in which any aspect of the program, the trainee’s educational path, or other concerns could be discussed in a private setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations